Social selection acts on behavior and body mass but does not contribute to the total selection differential in eastern chipmunks. (24th November 2019) - Santostefano, Francesca; Garant, Dany; Bergeron, Patrick; Montiglio, Pierre‐Olivier; Réale, Denis
Abstract: Through social interactions, phenotypes of conspecifics can affect an individual's fitness, resulting in social selection. Social selection is assumed to represent a strong and dynamic evolutionary force that can act with or in opposition to natural selection. Few studies, however, have estimated social selection and its contribution to total selection in the wild. We estimated natural and social selection gradients on exploration, docility, and body mass, and their contribution to selection differentials, in a wild eastern chipmunk population ( Tamias striatus ). We applied trait‐based multiple regression models derived from classical phenotypic selection analyses, which allowed us to include several social partners (i.e., neighbors). We detected social selection gradients on female docility and male body mass, indicating that female with docile neighbors and males with large neighbors had lower fitness. In both sexes, social selection gradients varied with the season. However, we found no phenotypic assortment or disassortment for the studied traits. Social selection gradients, therefore, did not contribute to total selection differentials, and natural selection alone could drive phenotypic changes. Evaluating the factors that drive the evolution of the covariance between interacting phenotypes is necessary to understand the role of social selection as an evolutionary force.